Data from study on autumn destabilization of deep porewater CO2 store in a northern peatland driven by turbulent diffusion - Campeau, Audrey (Swedish University of Agricultural Sciences, 2021)
This dataset has been collected to investigate dynamics in peat porewater CO2 concentration at Degerö Stormyr, Sweden. It contains hourly measurements of porewater CO2 concentration, temperature at different depths along a vertical peat profile. Hourly measurements of groundwater table position, stream discharge and stream CO2 concentration at the peatland outlet are also included along with meteorological and C exchange measurements collected via eddy-covariance at the Degerö Stormyr ICOS station. The data is used in part to calculate apparent vertical diffusion coefficient in peat porewater and buoyancy frequency. All analysis were performed on R code. Scripts can be provided upon request to the corresponding author.

Datauppsättningen har samlats in för att undersöka dynamik i torvporvattens CO2 -koncentration vid Degerö Stormyr, Sverige. Data består bland annat av mätningar av CO2 –koncentration i porvatten och temperatur på olika djup längs en vertikal torvprofil, per timme. Data används delvis för att beräkna skenbar vertikal diffusionskoefficient i torvporvatten och flytfrekvens. All analys utfördes på R -kod. R-skript kan tillhandahållas på begäran till motsvarande författare.

Mer information på den engelska katalogsidan.
Datauppsättning för forskningsartikel: Autumn destabilization of deep porewater CO2 store in a northern peatland driven by turbulent diffusion.
Keywords: repeated measures; peat soil; carbon dioxide; koldioxid; peat swamp forest; water chemistry; peat bog; peatland; water temperature; climate; klimat; groundwater level; meteorology; meteorologi; Environmental monitoring facilities; Anläggningar för miljöövervakning; Soil; Mark; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Environmental Sciences; Miljövetenskap; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi; Environment; Miljö; Inland Waters; Sjöar och vattendrag